Efficiency in the provision of municipal nursing- and home-care services: The Norwegian experience - Espen Erlandsen; Finn R. Førsund (University of Oslo, Department of Economics, 1999)
The municipalities in Norway are responsible for providing care for their inhabitants in need. The care takes two main forms: institutionalised care in nursing homes and home-based care. Based on cross-section data for 1995 for 471 municipalities the efficiency of the care activity is investigated using the non-parametric DEA approach. Quality is regarded as very important for the amount of resources spent, but measures that capture quality are very hard to come by. The available data source allows only single-bed rooms as a quality indicator for nursing homes and only number of clients in various age groups as basis for output variables in general. For the three basic activities nursing homes, home based care and home based medical treatment nine output variables are defined based on three age groups; 0-17, 18-79, and 80+. The forming of age groups are designed to reflect the severity of need for care in order to take care of the “patient-mix”- effect. In addition, net throughput of clients as a variable catching short-term clients in nursing homes is used as an output. Labour in man-years and other current expenses are the inputs. There are no data for capital inputs, like buildings and equipment. Significant differences in efficiency between municipalities are revealed and efficient peers identified that can be studied by municipalities wanting to improve performance. – Nursing ; Home care ; Efficiency ; DEA
Keywords: D24; H42; I12; L84; 330; Pflegedienst; Norwegen